Strategi Guru BK (Bimbingan Konseling) dalam Meningkatkan Kedisiplinan Siswa di SMA Al-Hidayah (International Forum of Researchers and Lecturers, 2025)
Student discipline remains a significant issue in education, including at SMA Al-Hidayah, where various violations such as tardiness, non-compliance with school rules, and lack of academic responsibility are still commonly found. This study aims to describe the forms of disciplinary violations committed by students, the strategies employed by school counselors, and the role of guidance and counseling (BK) teachers in improving student discipline. A descriptive qualitative approach was used, with data collected through interviews, observations, and documentation. The results show that common violations include arriving late, not wearing the proper uniform, and failing to complete assignments. The strategies applied by BK teachers include preventive approaches, curative measures, positive reinforcement, and collaboration with subject teachers and parents. The role of the BK teacher is central, acting as a facilitator, mentor, and mediator in the development of student discipline. These findings support existing theories that emphasize humanistic, consistent, and collaborative approaches as effective methods for fostering internal awareness of discipline among students. With well-planned strategies and consistent implementation, school counselors can become key agents in creating a culture of discipline within the school environment.